Necro citizenship : death, eroticism, and the public sphere in the nineteenth-century United States - Castronovo, Russ, 1965- (New Americanists., 2001)
Argues that the category of death was a central part of the concept of citizenship in the nineteenth-century U.S., and that the particular form of that construction functioned to naturalize white males as ideal citizens.